1996
DOI: 10.1021/ja960468v
|View full text |Cite
|
Sign up to set email alerts
|

True and Spectator Intermediates in Catalysis:  The Case of Ethanol Oxidation on Molybdenum Oxide As Observed by in Situ Laser Raman Spectroscopy

Abstract: A high-throughput laser Raman spectrometer is used to detect adsorbed ethoxide species during the catalytic oxidation of ethanol over supported molybdenum oxide at atmospheric pressure. Two different species are observed, a true reaction intermediate and a relatively inert spectator on the surface. Steady-state and dynamic experiments indicate that the reactive species is associated with ModO terminal bonds on the surface, while the spectator is associated with Mo-O-Mo bridging bonds. Deuterium isotopic substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…MoO 2 may be used as catalyst for the oxidation of ethanol to acetaldehyde [8], but also as precursor for the preparation of Mo nanofibers. Zach et al [9] reported the synthesis of molybdenum nanofibers, with diameters between 13 nm and 1 m and up to 500 m long, by H 2 reduction at 500 • C of MoO 2 nanofibers electrodeposited.…”
Section: Introductionmentioning
confidence: 99%
“…MoO 2 may be used as catalyst for the oxidation of ethanol to acetaldehyde [8], but also as precursor for the preparation of Mo nanofibers. Zach et al [9] reported the synthesis of molybdenum nanofibers, with diameters between 13 nm and 1 m and up to 500 m long, by H 2 reduction at 500 • C of MoO 2 nanofibers electrodeposited.…”
Section: Introductionmentioning
confidence: 99%
“…Oyama et al. using deuterium isotopic substitution experiments in the oxidation of ethanol to acetaldehyde . In the step 3 nascent hydroxyl group bonded with the titanium cations which recombines with another OH leads to removal of H 2 O and formation of vanadyl oxygen species and the adsorbed benzaldehyde can desorb as a product (step 4) and leaves the catalyst as it is.…”
Section: Resultsmentioning
confidence: 99%
“…Emission bands locating in the violet-blue, green, and red region can be observed (Figure 3 ). Two emission peaks in the region of 520-538 and 542-560 nm, originated from the transition 2 (Figure 4 a), indicating that at least three and two infrared photons have been involved for the emission of each, one violet and red upconversion photon, respectively. However, all of the three emission bands are much weaker than the green emission band as their relatively ineffi cient upconversion processes.…”
Section: Resultsmentioning
confidence: 99%
“…Molybdenum oxides (MoOx), especially nanocrystalline MoO 3 exhibit attractive catalytic, photochromic and electronic properties, as well as a great potential for various applications. MoO 3 has attracted considerable attention from researchers in the field of catalysts, chemical sensors, solid lubricants, thermoelectric materials, bioscience, and especially in the recent years in electronic device applications such as field emitters, light‐emitting diodes, and photovoltaics . As a hole‐extracting layer, MoO 3 was demonstrated to improve device performance in solar cells due to its favorable electronic and optical properties .…”
Section: Introductionmentioning
confidence: 99%